Character Formation through Civic Education Learning Process - Pangalila, Theodorus; Tuerah, Javier; Umar, Mardan (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is currently experiencing a characterization characterized by national issues such as corruption, violence in the name of religion, and riots between students. All the problems faced by the Indonesian people lead to the low quality of Indonesian human resources. The purpose of this study is to find out how the formation of character occurs through learning citizenship education. This research is a type of qualitative research, with the main data sources being book sources and articles that are relevant to the topic of character formation. The research found that efforts to strengthen character through the civic education learning process have been going on for a long time and are integrated into every curriculum in Indonesia. This research recommends further research on the character-based civic education learning model.